Associação entre periodontite e fatores sistêmicos e sociodemográficos - Barbosa, Carla Gabriela Damasceno (Brasil, 2023)
There is vast scientific evidence on the epidemiology of periodontal diseases and how they affect a large population. These studies, for the most part, are focused on the host response to the exacerbation of microorganisms present in periodontal disease as a determining factor. However, studies that emphasize the importance of the role of association factors in determining predisposition to periodontitis are also very relevant for understanding the pathogenesis, as well as its prevention and treatment. Systemic, sociodemographic and psychosocial factors may be associated with the occurrence, extent and severity of periodontitis. The objective of this study was to evaluate the relationship between the variables age, gender, socioeconomic status, Type II Diabetes Mellitus and smoking with periodontal condition, in the population of patients treated at the Faculty of Dentistry (FAO) of the Federal University of Amazonas (UFAM). This is an observational, cross-sectional study, based on the verification of medical records of patients with periodontal diagnosis in the period from 2018 to 2022. A logistic regression analysis was performed between the explanatory variables and the outcome, including the term of interaction between variables. In all statistical tests, the significance level will be 5%. The average age of the individuals was 48.86±14.09 years, with a predominance of females (55.41%), single marital status (45.27%) and self-declared brown color (69.01%). Most of the population had completed high school (56.30%) and the average minimum wage was 1.72±1.49. Regarding the classification of periodontitis, there was a prevalence of 55.41% of stages III and IV. The prevalence of smokers was 9.46% and former smokers 29.05%. With regard to the diagnosis of Type II Diabetes, 9.46% of the individuals had it. Plaque index was high with a mean of 52.66±29.85, as well as bleeding on probing with a mean of 39.53±26.73. The mean number of pocket depth ≥5mm and clinical level of interproximal insertion ≥4mm was 7.49±12.36 and 18.20±15.59, respectively. The number of patients with dentition considered functional (≥20 teeth) was 54.05%. In the regression analysis, an association was found between diabetes and severe periodontitis, adjusted for the number of teeth and bleeding on probing. Conclusion: the population of patients analyzed is predominantly female, self-declared brown, with low socioeconomic status and high prevalence of tooth loss. The most prevalent periodontitis is severe periodontitis, and, in the analyzed sample, Diabetes was associated with severe periodontitis.